(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objectives and Methods: The market of traditional and complementary medicine is rapidly increasing in developing countries. Preference, referral practice and acceptance of alternative forms of medicine among allopathic practitioners is assessed in this cross sectional study using semi structured questionnaire method. Allopathic doctors (n=258) working in tertiary care setup were included in this study by convenient sampling with prior consent taken. Both google form and hard copy format was made available. Data was entered in XL spread sheet and analysis was done using SPSS version 26. Results: Among the various alternative system of medicine, yoga was the highest preferred (48.8%) followed by siddha (33.3%), ayurveda (30.6%), homeopathy (22.5%), herbal medicine (20.2%), acupuncture (12.8%) and finally unani with least preference of 2.7%. Combination of allopathy and alternative medicine was preferred by 46.9% whereas 21.3% did not prefer, 30.6% were not sure. Skin problem is the main condition for which doctors refer the patients to complementary medicine. Further the study showed 45.7% of allopathy doctors have accepted the idea of practicing complementary medicine within allopathy hospitals. The results showed 25.2% of doctors feel that allopathy has more side effects, whereas 18.2% of doctors feel that alternative forms of medicine have more side effects. Conclusion: Practicing Doctors of allopathic medicine do prefer AYUSH systems and complementary medicine and recommend it to their patients too. However, many doctors want evidence to practice complementary medicine as they are not aware of the safety and efficacy of alternative forms of medicine.